Role of the dentist in the management of patients with HIV/AIDS - G. A. Agbelusi; A. A. Wright (Nigerian Dental Association, 2007)
The clinical problem of HIV infection poses one of the greatest challenges to Health Care Workers (HCW) all over the world. AIDS, since its appearance in 1981 has spread to become a major cause of premature death and so far, a cure is yet to be found. Its mode of spread poses special danger to HCW particularly the dentists who have close contact with the patients. This paper examines the relationship between HIV and dentistry; the role of the dentist, the size of the pandemic and its implication to the dental profession, especially regarding infection control. Ethical issues in the management of HIV patients are also addressed by highlighting areas of conflict. The aim of this paper is to educate and sensitize the dentist and the dental team to these issues as they relate to occupational exposure and suggest ways of resolving areas of conflict. This is to ensure that neither patient management, the health of the HCW nor their practice is compromised in any way.